Clinical and Virologic Outcomes of Baloxavir Compared with Oseltamivir in Pediatric Patients with Influenza in Japan - Nobuhisa Ishiguro; Ichiro Morioka; Takashi Nakano; Atsushi Manabe; Keiko Kawaguchi; Shintaro Tanaka; Masahiro Kinoshita (Infectious Diseases and Therapy)
Abstract Introduction Baloxavir marboxil, a cap-dependent endonuclease inhibitor, has proven efficacy against influenza. There are limited comparative data between baloxavir and oseltamivir in Japanese pediatric patients with influenza. We evaluated the clinical and virologic outcomes and assessed safety of baloxavir compared with oseltamivir for treating influenza in Japanese patients aged 6 to < 12 years. Methods In this open-label, randomized (2:1) trial, patients received oral administration of either a single dose of baloxavir or a twice-daily 5-day course of oseltamivir. The primary efficacy endpoint was time to illness alleviation (TTIA). Other efficacy and safety endpoints were also assessed. Results Of 199 enrolled patients (mean age: 9 years), 195 were randomized (baloxavir, n = 128; oseltamivir, n = 67). Of these, 50.8% had influenza A/H3N2, 37.4% influenza B, and 10.3% influenza A/H1N1pdm. Median (95% confidence interval) TTIA was 44.8 (41.5, 69.7) h and 72.2 (50.9, 96.9) h in the baloxavir group and the oseltamivir group, respectively. The median time to first cessation of virus shedding was shorter in the baloxavir vs. oseltamivir group (48.0 vs. 192.0 h). Before treatment, one patient had PA/I38X virus infection at baseline. After treatment, PA/I38X viruses were observed in 12 patients (11 A/H3N2 and 1 A/H1N1pdm). No serious adverse events, including death, were observed in either group. Conclusion In this study, baloxavir showed the potential for shortening of symptom duration compared with oseltamivir, which suggests baloxavir as an important treatment option for patients with influenza aged 6 to < 12 years. Trial Registration The study was registered at the Japan Registry of Clinical Trial (jRCT) on November 11, 2020 (registration no. jRCTs011200011).